(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The research analyzes the qualitative and temporal configuration of secular and confessional education with the identification of positive aspects and critical points. In the authors’ opinion, socio-cultural analysis can serve as a theoretical platform for comprehending pedagogical experience and providing an understanding of the theoretical and methodological basis of the educational models under consideration. The results of the analysis allow the authors to come to the conclusion that a comparative analysis of secular and confessional education provides a wide variety of options that are analyzed in close relation with the genesis of culture, science, and social thought, based on different priorities, and thus, to identify the main models of education. Carrying out the research of the specifics of the secular and confessional education models’ functioning, implemented in various world educational practices, the authors came to the conclusion that there is a «coordinate system» that determines the nature of existing models. This coordinate system includes: a historically established type of relationship between the state and religious associations; national and cultural characteristics of the country; the role of traditional religious values in the life of the people; specificity of legal systems, percentage ratio of the number of social and confessional groups. Key words: education, secular model of education, confessional model of education, dialogue of cultures.